Direct Cell Labeling to Image Transplanted Stem Cells in Real Time Using a Dual‐Contrast MRI Technique. (14th August 2017) - Ngen, Ethel J.; Kato, Yoshinori; Artemov, Dmitri
Abstract: Exogenous direct cell labeling with superparamagnetic iron oxide nanoparticles (SPIONs) is currently the most employed cell‐labeling technique for tracking transplanted cells using magnetic resonance imaging (MRI). Although SPION‐based cell labeling is effective for monitoring cell delivery and migration, monitoring cell survival is still a challenge. This unit describes an MRI technique that permits detection of the delivery, migration, and death of transplanted cells. This dual‐contrast technique involves labeling cells with two different classes of MRI contrast agents, possessing different diffusion coefficients: SPIONs (T2 /T2 * contrast agents, with lower diffusion coefficients) and gadolinium chelates (T1 contrast agents, with higher diffusion coefficients). In live cells, where both agents are in close proximity, the T2 /T2 * contrast predominates and the T1 contrast is quenched. In dead cells, where the cell membrane is breached, gadolinium chelates diffuse from the SPIONs and generate a signature T1 contrast enhancement in the vicinity of dead cells. © 2017 by John Wiley & Sons, Inc.